On the ecological recognition of Butia palm groves as integral ecosystems: Why do we need to widen the legal protection and the in situ/on-farm conservation approaches? - Sosinski, Ênio Egon; Urruth, Leonardo Marques; Barbieri, Rosa Lía; Marchi, Marene Machado; Martens, Silvano Gildo (Land use policy, 2019)
Brazilian environmental legislation provides protection to native flora in different ways. However, the predominantly non-forest ecosystems of Brazil have no specific legislation protecting their ecological particularities. Many authors have emphasized the relevance of recognizing the ecological importance of non-forest ecosystems and the need to include them in conservation priorities. Southern Brazil, northeastern Argentina and Uruguay harbor one of the most fascinating ecosystems of the southern South American grasslands, the Butia palm groves. These are natural non-forest ecosystems dominated by populations of Butia species (Arecaceae) scattered through the grassy matrix. Land conversion to agriculture, silviculture and urban sprawl are the greatest threats to these palm species. For instance, in the southern Brazilian Pampa grasslands where palm groves were once very abundant, 26% of the natural grasslands have been lost over a period of 30 years. This significant habitat loss is aggravated by the protection of only 0.4 per cent of the Pampa biome within legally designated areas. Furthermore, palm groves are not recognized in Brazilian official vegetation classification systems. Therefore, there is a need to recognize non-forest ecosystems as ecologically integral entities. This implies the necessity of understanding, for instance, that preservation of palm groves is critical to re-establish the natural processes of these ecosystems, i.e., to begin to support the natural renewal process of palm groves, jointly with conserving the natural grassy matrix and all its diverse flora and fauna. Public policies focusing on these ecosystems and species must include promotion of sustainable use of their products, using their economic value to increase interest in their conservation. Practices that ensure the renewal of populations, such as conservative grazing management and ecosystem restoration, also need to be implemented.